The Method of Artistic Mystification in Ransmayr’s Novel “The Last World” - Kovtun, Natalia (Respectus Philologicus, 2014)
The article proposes a new interpretation of the iconic novel by Austrian writer Christoph Ransmayr,The Last World (Die letzte Welt, 1988), recognized as the best European prose text of the late 1980s. The quest is the basis of the plot of the novel, the interpretation of Ovid’s mystified and mythologized poem, “Metamorphoses.” Various readings of the famous text can be interpreted as methods of externalization, verification of the author’s self-image, or attempts to approximate the truth of the primary meaning revealed in Genesis. The chosen foreshortening of the study reveals the forms of the author’s self-reflections through image-masks (hero—narrator—“commentator”—reader), a narrative story (facts of artistic reality—events of the story—the reading process—“commenting”), mystification of texts (works of world literature—character/narrator books—reader/“interpreter” texts), and a system of commentaries on them. Hero/storytellers, offering different interpretations of the missing poem, implement their own understanding of reality, one that requires further discussion and examination. The process of cognition is the essence of reading; interpretations of prior texts and the creation of new ones disprove the main thesis of postmodernism about the reticence and hermeticity of works of literature. In this novel, Ovid reveals the mystery of elusive time, heaven, and hell. The process of empathy, the narrator’s and reader/listener’s co-creation, bring a closer understanding of the metaphysical foundations of being.